A Comparative Study on various Flight Termination System Technologies - Priyadarshini, Sushree; Gourab, Mohapatra Kumar; Mandal, Utpal; Roy, Angshuman (Defence Science Journal, 2023)
In a test range, a Flight Termination System (FTS) plays a prominent role in protecting range and flight personnel along with surrounding area population in case the flight vehicle is out of its trajectory range and possesses a threat to surrounding. An efficient FTS should posses high Signal to Noise Ratio, link robustness to ensure reliable communication between ground transmitting and onboard receiving systems and should be immune to interference. This article presents a detailed report on the requirement and features of FTS & technologies used in it. Techniques such as tone based, code based and Code Division Multiple Access (CDMA) are considered. Analysis of RF spectrum, gain and noise figure measurement and channel power are presented. Advanced methods like Enhanced Flight Termination System (EFTS) and Autonomous Flight Termination System (AFTS) are considered which show supportable and upgradable technologies, better range understanding, unique vehicle id & higher data rate. AFTS being self-reliant provides superior performance in terms of GPS, launch responsiveness, multiple flight vehicle control and auto pilot.